A house like a 'musical instrument' - Heilgendorff, Simone (Muzikološki zbornik, 2011)
In Berlin (Germany) there has been an exceptional project of a house for contemporary music and new music theatre (COB/ZOB) offering a variety of solutions for an urban not yet settled vibrant cultural 'zone', where artistic activity and everyday life meet. Tied back to the model of ancient agoras the building was mapped out during 2001 collaboratively by a team of specialists in New Music and advanced performative architecture. It can be detected - even though it has not been built - as an ongoing and creative reference project.
Keywords: architecture; arhitektura; Berlin; contemporary music; Kühn, Oliver; performative turn; performativni zasuk; Rocholl, Andreas; sodobna glasba; urban studies; urbane študije